Bacterial Contamination of Medical Masks Across Different Wear Durations in Campus Setting - Wulan Fitriani Safari; Achmadi; Intan Kurniawati Pramitaningrum; Silvi Almadhita Saphira; Amar Rizqi Kusuma; Sheila Camelia (UNIVERSITAS PGRI MADIUN, 2026)
Medical masks play an important role in minimizing infection risk; however, they may also act as reservoirs for bacterial contamination. Mask wear duration is a key factor influencing microbial accumulation. While previous studies have focused on healthcare, industrial, or community settings, limited attention has been given to campus environments, where prolonged mask use is common among students and staff. This study aimed to evaluate bacterial contamination on disposable medical masks across different wear durations in a campus setting. This study involved 10 student who wore disposable medical masks for 0 (control), 3, and 6 hours under campus conditions. Bacterial contamination was assessed using the Plate Count Agar (PCA) method following serial dilution, and results were expressed as CFU/cm². Data were analyzed using using the Kruskal–Wallis test. The results showed a progressive increase in bacterial contamination with longer mask wear duration, from 0 hours (0 ± 0 CFU/cm²), to 3 hours (34.8 ± 28.04 CFU/cm²), and sharply at 6 hours (7297.59 ± 9552.08 CFU/cm²). Significant differences were observed between wear durations. In conclusion, extended mask wear duration may increase the risk of bacterial accumulation; therefore, appropriate mask replacement practices are recommended to support personal hygiene and health protection